Is Voluntary Administration Failing Companies? An Investigation into the Operation of Voluntary Administration in New Zealand from Inception to 2019 - Ellice, Sebastian (Victoria University of Wellington Law Review, 2021)
This article investigates the operation of voluntary administration in New Zealand from inception in 2007 to 2019. Voluntary administration is a formal insolvency procedure that is intended to maximise an insolvent company’s chances of rehabilitation. Research undertaken for this article suggests that voluntary administration is not operating as was intended. It appears to have been underused and largely ineffective as a business rehabilitation mechanism. This article suggests that contributing reasons for the findings of the research include cost barriers for small businesses, a lack of confidence on behalf of creditors, and a misuse of voluntary administration by company directors. It proposes that useful reforms would be to reduce cost barriers and place limitations on when and how the procedure can be used.